(untitled) (St. Louis, Mo., 2014)
Prepare for success on your HESI exit exam and the NCLEX-RN®! HESI Comprehensive Review for the NCLEX-RN® Examination, 4th Edition provides a comprehensive, all-in-one review of the information you need to know. Written in an easy-to-read outline format, this study tool breaks down chapters by clinical areas and concepts emphasized on the NCLEX-RN exam. Rationales are provided for any incorrect answers or areas of weakness. The companion Evolve website offers approximately 700 practice questions, giving you valuable practice in the same electronic testing format you will experience on your nursing school exit exam and on the NCLEX-RN exam.
Keywords: Nursing,Nursing,Điều dưỡng,Điều dưỡng; Examinations,Study guides,Examinations, questions, etc.,Hướng dẫn học tập,Thi cử,Câu hỏi và bài tập